2023
DOI: 10.3390/foods12081723
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Storage Melatonin Application on the Standard, Sensory, and Bioactive Quality of Early Sweet Cherry

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) is involved in multiple functions in plants. However, its role in some metabolic pathways and exogenous application’s effect on fruits is still unclear. Furthermore, the effects of pre-storage melatonin treatment on sensory traits and consumer acceptance of cherries have yet to be studied. For this reason, the early sweet cherry cultivar ‘Samba’ harvested at the commercial ripening stage was treated with different melatonin concentrations (0.1, 0.3, and 0.5 mmol L−1) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…After 40 days of postharvest storage, M0.5 'Primetime' plums had a less dark exocarp colour; lower RI, weight loss and ethylene production rate; and, in addition, higher firmness, anthocyanin content and TAA (Table 2), showing better fruit acceptance potential and senescence delay. These results agree with Agham et al [17], Arabia et al [7,23], Xia et al [24,42], Carrión-Antolí et al [11,12], Yan et al [46] and Cortés-Montaña et al [53], who proposed melatonin treatment as a potential strategy to maintain fruit quality, due to its implication in the reduction of biotic and abiotic stress, weight loss, incidence of chilling injury and activation of bioactive systems that promote free radical scavenging, which allows for increasing the shelf life of the fruit and reducing food waste.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…After 40 days of postharvest storage, M0.5 'Primetime' plums had a less dark exocarp colour; lower RI, weight loss and ethylene production rate; and, in addition, higher firmness, anthocyanin content and TAA (Table 2), showing better fruit acceptance potential and senescence delay. These results agree with Agham et al [17], Arabia et al [7,23], Xia et al [24,42], Carrión-Antolí et al [11,12], Yan et al [46] and Cortés-Montaña et al [53], who proposed melatonin treatment as a potential strategy to maintain fruit quality, due to its implication in the reduction of biotic and abiotic stress, weight loss, incidence of chilling injury and activation of bioactive systems that promote free radical scavenging, which allows for increasing the shelf life of the fruit and reducing food waste.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, producing high-quality fruit at harvest ensures better postharvest storage. Melatonin has been shown to have positive effects in delaying senescence and preserving the sensory and nutritional quality of different types of fruits during postharvest [53]. This is of considerable economic importance worldwide, as it could contribute to reducing food waste [17].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8]29,30 It has been found that the application of exogenous melatonin can promote the accumulation of endogenous melatonin and regulate various metabolic pathways in fruits, enhancing postharvest quality and extending shelf-life. 6 Authors such as Wang et al, 31 Carrión-Antolí et al 9 and Cortés-Montaña et al 13 demonstrated that fruit that had been treated with melatonin showed a better postharvest life. Our study revealed that the endogenous concentration of melatonin increased proportionally to the concentration applied.…”
Section: Discussionmentioning
confidence: 99%
“…TSS, TA and RI were determined as described by Cortés-Montaña et al 13 Identification and quantification of OAs were carried out according to the protocol described by Serradilla et al 14 Results were expressed as g kg −1 FW. Firmness and colour were measured on two opposite cheeks of 30 independent fruits of each treatment as described by Cortés-Montaña et al 13 Firmness was tested on the fruit with a Stable Micro Systems TAXT2i texturometer (Aname, Pozuelo, Madrid, Spain) by a 3% compression test using a 25 mm flat base probe. The displacement speed of the test was 0.2 mm s −1 , and results were expressed as N mm −1 .…”
Section: Physico-chemical Parametersmentioning
confidence: 99%
“…Among fruits, cherries, strawberries, and wine grape skins contain the highest amount of melatonin [ 128 ]. Research carried out with cherry varieties has shown an exceptionally high melatonin content in cherries, which suggests that cherries can be a natural source of melatonin and become suitable for the development of melatonin-rich functional foods [ 129 ]. Sources of the highest tryptophan content are not typical ingredients of the Western diet (just for information: the fatty meat of seals, their kidneys, and the beluga whale) [ 130 ].…”
Section: Sleep and Menopausementioning
confidence: 99%